Pengembangan Lembar Kerja Siswa Berbasis Etnomatematika Tenun Timor pada Materi Pola Bilangan - Hermina Disnawati; Selestina Nahak (Universitas Hamzanwadi, 2019)
This research was motivated by the fact that there are no available learning resources in accordance with the conditions and situations of everyday students in the border area. This research aims to (i) design student’s worksheets which are valid and practical; (ii) determine the potential effects or the effectiveness of students worksheet toward student outcomes in learning number pattern. The development research method was used which is consist of preliminary study and formative evaluation. Data is collected through documentation studies, walkthrough, tests, observations, questionnaires, and interviews. The results of the study show that: (i) this research has produced student’s worksheets in line with ethnomathematics of Timor-based weaving valid and practical. Validity criteria are obtained from the validator's assessment which examines three aspects namely construct, content and language; Practical criteria are based on the results of trials in the small group by involving 4 students with different abilities and 31 students in the field test stage; and (ii) Student’s worksheet also has potential effect toward student’s achievements in learning the concepts and applications of number pattern in solving problems. There were 26 of 31 students (83.85%) which fulfill the minimum criteria while 16.12% of them still below the standard. It means that student’s outcomes on number pattern were highest than schools standard (70%).